Pandangan Sheikh Mahmud Syaltut Tentang Agama Dan Negara - Nasuha Abu Bakar (LP2M Universitas PTIQ Jakarta, 2016)
The relationship between religion and the state has always been a hot topic in discussions about constitutionality, including the East Mufassir. The following article contains the views of Sheikh Mahmud Syaltut Yang who according to religion (Islam) and the state has a very close and strong relationship, like a foundation and a building. A building cannot be realized without a foundation, and vice versa, the foundation without a building, will not be shaped. This view of Sheikh al-Azhar is in some ways compatible with al-Ghazali’s view which illustrates the relationship between religion (Islam) and the state like twins that cannot be separated and cannot be differentiated. Therefore these two Islamic leaders assume that it is impossible to grow and develop religion if it is not accompanied by the establishment of the state, and vice versa will not be formed if the state does not pay attention to religion, because both of them need each other and are needed.